Самостоятельная работа учащихся в малокомплектной школе - Дощанова, Б.М. (My University, 2016)
Small schools – is an organization of education with a small contingent of students, combined class and sets and specific form of training sessions’ organizing. Independent work of students in small schools – is a form of their cognitive activity’s organizing, requiring demonstration of activity, creativity and initiative in problems solving. Correctly and efficiently organized independent work of students of a class – is normal condition of learning activities of students of another class, and it is a requiring component of the lesson in small schools. From the teacher’s ability to alternate training and independent work under its management, largely depends on the lesson’s success.
Keywords: small schools combined class-set; self study; nontraditional method of work; the psychological characteristics of students; the alternation of the two components work under the guidance of teachers